A Princess’s Defiance In Brave Movie - Fransiska Nur Ariani (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study examines the construction and function of female masculinity in the animated film Brave (2012), focusing on how the protagonist, Merida, negotiates her non-traditional identity within a patriarchal familial structure. Using Judith Butler’s Gender Performativity Theory and R.W. Connell’s framework of masculinity as a social construct, this paper analyzes how Merida’s expressions of physical prowess, independence, and defiance are not merely isolated traits but are dynamically shaped by her interactions with her parents, Queen Elinor and King Fergus. While Elinor represents the rigid enforcement of traditional domesticity, Fergus acts as an unwitting cultural archetype of hegemonic masculinity that Merida emulates. Through qualitative textual and dialogue analysis of the film’s screenplay, the findings reveal that Merida’s masculine performance serves a dual purpose: it acts as a mechanism for personal identity formation and operates as a catalyst for systemic cultural change within her kingdom, redefining the boundaries of female agency in contemporary media.